The future prospect of metal-organic frameworks for theranostic purposes in brain disorders - Mahnaz Ahmadi (Nanomedicine Journal, 2025)
The burgeoning field of nanoscale metal-organic frameworks (NMOFs) has captured substantial attention within the biomedical fields, prompting a shift towards exploring their potential in diagnosis and treating brain disorders. This narrative letter delves into the limited research encompassing NMOF-mediated drug delivery to the brain for neurological conditions compared to other applications. Despite significant strides in diagnosing and treating brain ailments utilizing NMOFs, challenges persist, notably the formidable blood-brain barrier (BBB) hindrance, stability issues, and cost considerations. Enhancing NMOF efficacy requires strategic functionalization, eco-friendly synthesis methodologies, and rigorous toxicity assessments. Overcoming these obstacles involves tailoring NMOF properties for improved BBB penetration and physiochemical stability, alongside meticulous biocompatibility evaluations. To advance NMOF applications in neurological theranostics successfully, concerted efforts towards refining safety, efficiency, precise delivery, and cost-effectiveness are imperative. Addressing these challenges will pave the way for translating this promising technology into practical clinical settings, facilitating enhanced precision and efficacy in neurology.